2018
DOI: 10.3389/fpsyg.2018.00875
|View full text |Cite
|
Sign up to set email alerts
|

How Does Consecutive Interpreting Training Influence Working Memory: A Longitudinal Study of Potential Links Between the Two

Abstract: With an intention to contribute to the issue of how language experience may influence working memory (WM), we focused on consecutive interpreting (CI), analyzed its potential links with WM functions and tested these links in a longitudinal experiment, trying to answer the specific question of how CI training may influence WM. Two comparable groups of Chinese learners of English received either CI or general second language (L2) training for one semester, and were tested before and after the training with the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 53 publications
(87 reference statements)
1
31
0
2
Order By: Relevance
“…Research into the first question has assessed the WM capacity of interpreters with different levels of expertise, such as trained or professional interpreters, bilinguals, and SI students. The results indicate that interpreters with higher level of expertise outperform non-interpreters in WM capacity (e.g., Padilla Benitez et al, 1995 ; Christoffels et al, 2006 ; Shen and Liang, 2015 ; Dong et al, 2018 ). However, Liu et al (2004) and Injoque-Ricle et al (2015) claimed that no significant difference in WM exists across professional interpreters with different length of experience.…”
Section: Introductionmentioning
confidence: 91%
“…Research into the first question has assessed the WM capacity of interpreters with different levels of expertise, such as trained or professional interpreters, bilinguals, and SI students. The results indicate that interpreters with higher level of expertise outperform non-interpreters in WM capacity (e.g., Padilla Benitez et al, 1995 ; Christoffels et al, 2006 ; Shen and Liang, 2015 ; Dong et al, 2018 ). However, Liu et al (2004) and Injoque-Ricle et al (2015) claimed that no significant difference in WM exists across professional interpreters with different length of experience.…”
Section: Introductionmentioning
confidence: 91%
“…Firstly, WM has a time limitation in the sense of information storage and processing; likewise, interpreting involves immediacy that is not present during translation. A recent longitudinal study by Dong, Liu and Cai (2018) revealed that consecutive interpreting students show more progress than general L2 students in WM using an n-back task. We hypothesised that the immediacy factor may lead to better WM performance in interpreting groups.…”
Section: The Present Studymentioning
confidence: 99%
“…Updating and WM spans have been investigated for the issue of an interpreter advantage in WM. Based on Cowan's (1988) process model of WM, Dong, Liu and Cai (2018) analyzed in detail similarities between consecutive interpreting features (e.g., recalling in another language what has been heard in the input language) and features of WM updating and WM spans. They then predicted that consecutive interpreting training would first enhance WM updating and then WM spans.…”
Section: Empirical Findings: Effects Of Language Control In Interpretingmentioning
confidence: 99%